Sea-level variations during Marine Isotope Stage 7 and coastal tectonics in the eastern Seto Inland Sea area, western Japan. (15th October 2017) - Sato, Hiroshi; Ban, Fumika; Katoh, Shigehiro; Hyodo, Masayuki
Abstract: Relative sea-level (RSL) observations for Marine Isotope Stage (MIS) 7 were obtained from three sites (Higashinada, Kakogawa and Mitsu) of the eastern Seto Inland Sea area, western Japan. We evaluated the magnitude of sea-level highstands during MIS 7 and the local tectonics based on RSL records of this coastal area. For this purpose, we analyzed diatom assemblages and sedimentary sulfur, and carried out tephra analysis. We also constructed a linear age model to determine the depositional ages of the sediments using altitudes of astronomical age control points obtained mainly from the present diatom data. At the Mitsu site, RSLs were estimated to be −22.87 ± 0.50 m at the MIS 7.5 highstand peak (234.6 ka), below −20.17 m at 211.2 ka, and below −20.00 m at 209.9 ka. With a tectonic subsidence rate of 0.11 ± 0.02 m/ka since the Last Interglacial Maximum at the Mitsu site, the elevation of the tectonically corrected MIS 7.5 highstand peak may have been +2.94 ± 5.19 m. The tectonically corrected sea-level elevations during MIS 7.3 are inferred to have been below +3.06 ± 4.72 m at 211.2 ka and below +3.09 ± 4.70 m at 209.9 ka. Comparisons between the diatom-inferred RSLs and the isotopically derived sea-level curve indicate that the MIS 7.3 highstand peak was above −18 m and may have been lower than the MIS 7.5 and 7.1 highstands. Based on the isotopically derived sea-level curve and the RSL data from Higashinada and Kakogawa, a tectonic subsidence rate of 0.26–0.32 m/ka was derived for Higashinada and a tectonic uplift rate of >0.17 m/ka and <0.29 m/ka was derived for Kakogawa. A relative uplift rate of >0.43 m/ka and <0.61 m/ka was derived along the traverse from Higashinada to Kakogawa. The uplift rate derived for Kakogawa relative to Mitsu is > 0.26 m/ka and <0.42 m/ka. These values indicate the intensity of crustal movements associated with active faulting of the Rokko–Awaji fault system along this tectonically active coast.